ASSOCIATION OF ENDOTHELIAL NITRIC OXIDE SYNTHASE GENE POLYMORPHISMS WITH END-STAGE RENAL DISEASE - Ismayilova, Sh.G.; Ibrahimova, Sh.S.; Muradova, S.R.; Haziyev, E.I.; Safaraliyeva, L.Kh.; Humbatova, A.N.; Mammadova, A.P. (World of Medicine and Biology, 2025)
This study aimed to assess the association of the endothelial nitric oxide synthase 786T>C (rs2070744) and 894G>T (rs1799983) polymorphisms with end-stage renal disease risk in an Azerbaijani cohort. The study included 120 end-stage renal disease patients and 100 healthy controls. The results revealed that the T allele of the endothelial nitric oxide synthase 786T>C polymorphism significantly increased the risk of end-stage renal disease (p=0.002). Moreover, the T allele in both the endothelial nitric oxide synthase 786T>C and 894G>T polymorphisms was associated with a higher risk of macroalbuminuria (OR=5.93; p=0.013) and microalbuminuria (OR=2.56; p=0.024). These findings suggest that the T alleles in the endothelial nitric oxide synthase polymorphisms play a crucial role in chronic kidney disease progression, and genetic screening for these variants may help identify patients at greater risk for end-stage renal disease in Azerbaijani population.
Keywords: chronic kidney diseases; eNOS gene polymorphisms; T-786C; G894T; end-stage renal disease